Managing the consumption of death and digital media: The funeral director as market intermediary. Issue 7 (9th August 2019) - van Ryn, Luke; Meese, James; Arnold, Michael; Nansen, Bjorn; Gibbs, Martin; Kohn, Tamara
Abstract: A growing number of companies are offering digital products and services for use in funerals. Drawing on interdisciplinary research in Australia, the United Kingdom and the United States, we explore how funeral directors operate as intermediaries for these digital products and services. We critically examine the popular framing of the funeral industry as a "conservative" business and examine how funeral directors actively mediate between their clients and the companies offering innovative products and services. This study provides an account of current developments in the funeral economy as well as a broader narrative about how funeral industry professionals have engaged with technology.